Europan Molecular Indicators of Life Investigation (EMILI) for a Future Europa Lander Mission - Brinckerhoff, William B.; Willis, Peter A.; Ricco, Antonio J.; Kaplan, Desmond A.; Danell, Ryan M.; Grubisic, Andrej; Mora, Maria F.; Creamer, Jessica S.; Noell, Aaron; Stern, Jennifer; Szopa, Cyril; Freissinet, Caroline; et al. (Frontiers in Space Technologies, 2022)
The Europan Molecular Indicators of Life Investigation (EMILI) is an instrument concept being developed for the Europa Lander mission currently under study. EMILI will meet and exceed the scientific and technical/resource requirements of the organic composition analyzer identified as a core instrument on the Lander. EMILI tightly couples two complementary analytical techniques, based on (i) liquid extraction and processing with capillary electrophoresis and (ii) thermal and chemical extraction with gas chromatography, to robustly detect, structurally characterize, and quantify the broadest range of organics and other Europan chemicals over widely-varying concentrations. Dual processing and analysis paths enable EMILI to perform a thorough characterization of potential molecular biosignatures and contextual compounds in collected surface samples. Here we present a summary of the requirements, design, and development status of EMILI with projected scientific opportunities on the Europa Lander as well as on other potential life detection missions seeking potential molecular biosignatures in situ.